Straight to heaven: Rectitude as spatial representation of morality. (27th January 2018) - Pacilli, Maria Giuseppina; Pagliaro, Stefano; Spaccatini, Federica; Giovannelli, Ilaria; Sacchi, Simona; Brambilla, Marco
Abstract: Abundant literature in cognitive sciences has shown that morality is grounded in bodily experience. Four studies tested the perceptual association between the spatial dimension of straightness and the abstract concept of morality. Study 1 ( n = 61) employed an IAT and revealed an association between straight figures and moral related words. Study 2 ( n = 83) employed a similar paradigm and further revealed that the effect we found in Study 1 cannot be attributable to the general association between straight figures and positivity. Study 3 ( n = 64) revealed that participants showed a stronger preference for straight figures after recalling moral (vs. immoral) deeds. Study 4 ( n = 183) showed the specific role of morality, in this sense, as recalling sociable (vs. unsociable) deeds had no significant influence on figure preferences. A small‐scale meta‐analysis confirmed the robustness of our findings. Results are discussed in light of the embodiment theory.